Mortality of former crocidolite (blue asbestos) miners and millers at Wittenoom. Issue 8 (28th November 2007) - Musk, A W; de Klerk, N H; Reid, A; Ambrosini, G L; Fritschi, L; Olsen, N J; Merler, E; Hobbs, M S T; Berry, G
Abstract : Background: Blue asbestos was mined and milled at Wittenoom in Western Australia between 1943 and 1966. Methods: Nearly 7000 male workers who worked at the Wittenoom mine and mill have been followed up using death and cancer registries throughout Australia and Italy to the end of 2000. Person-years at risk were derived using two censoring dates in order to produce minimum and maximum estimates of asbestos effect. Standardised mortality ratios (SMRs) compare the mortality of the former Wittenoom workers with the Western Australian male population. Results: There have been 190 cases of pleural and 32 cases of peritoneal mesothelioma in this cohort of former workers at Wittenoom. Mortality from lung cancer (SMR = 1.52), pneumoconiosis (SMR = 15.5), respiratory diseases (SMR = 1.58), tuberculosis (SMR = 3.06), digestive diseases (SMR = 1.47), alcoholism (SMR = 2.24) and symptoms, signs and ill defined conditions (SMR = 2.00) were greater in this cohort compared to the Western Australian male population. Conclusion: Asbestos related diseases, particularly malignant mesothelioma, lung cancer and pneumoconiosis, continue to be the main causes of excess mortality in the former blue asbestos miners and millers of Wittenoom.